Agriculture and development, comparatively, in Brazil and Portugal and the emergence of productive alternatives - Sapia de Campos, Ricardo Luiz (2025)
The article discusses the emergence of “alternative” productive experiences in rural municipalities in Brazil, compared with cases in villages and towns in Alentejo, southern Portugal. It establishes a connection between experiences across the two continents by examining two models: the sugar-energy sector in Brazil and the so-called olive oil industry in Portugal. These experiences are approached through the lens of the “development” matrix, as well as through a perspective that values subjective aspects, in contrast to the objectivity of the “hegemonic” model present in both Portugal and Brazil. The arguments are developed through a comparison of current elements in these two contexts.